The Transatlantic Sixties Europe and the United States in the Counterculture Decade - Monteith (Ed.), Sharon (Amerika: Kultur - Geschichte - Politik, 2013)
This collection brings together new and original critical essays by eleven established European American Studies scholars to explore the 1960s from a transatlantic perspective. Intended for an academic audience interested in globalized American studies, it examines topics ranging from the impact of the American civil rights movement in Germany, France and Wales, through the transatlantic dimensions of feminism and the counterculture movement. It explores, for example, the vicissitudes of Europe's status in US foreign relations, European documentaries about the Vietnam War, transatlantic trends in literature and culture, and the significance of collective and cultural memory of the era.